Percepatan Pembangunan Block Kapal dengan Jam Lembur dan Menambah Tenaga Kerja Menggunakan Metode Time Cost Trade Off - maruf, fannani; Abdulrahim, Muslimin (TEKNIKA, 2023)
PT PAL Indonesia is the largest shipyard company in Indonesia whose main product is ships. One of the ships produced is the 60 m KCR type. The production process is in the Warship Division of PT PAL Indonesia. However, the construction process of the KCR 60 type ship produced by PT PAL Indonesia still has some problems that cause delays at certain stages. The delay occurred because there was indeed a limited manpower owned by the Construction department. For this reason, it is necessary to calculate again for optimal scheduling by accelerating activities in the critical trajectory that have been calculated using the CPM method. Then it is accelerated by increasing overtime work hours and increasing labor. So that the results of accelerating the duration of activities for overtime hours are 5 days faster while the addition of labor is 6 days faster. With additional costs in each acceleration of IDR 69,724,431 for the acceleration of overtime hours, while IDR 50,727,273 for the acceleration of labor addition.